Safety and efficacy of dedicated guidewire, microcatheter, and guide catheter extension technologies for chronic total coronary occlusion revascularization: Primary results of the Teleflex Chronic Total Occlusion Study. Issue 2 (28th September 2021) - Kandzari, David E.; Alaswad, Khaldoon; Jaffer, Farouc A.; Brilakis, Emmanouil; Croce, Kevin; Kearney, Kathleen; Spaedy, Anthony; Yeh, Robert; Thompson, Craig; Nicholson, William; Wyman, R. Michael; Riley, Robert; et al.
Abstract: Background: Description of procedural outcomes using contemporary techniques that apply specialized coronary guidewires, microcatheters, and guide catheter extensions designed for chronic total occlusion (CTO) percutaneous revascularization is limited. Methods: A prospective, multicenter, single‐arm study was conducted to evaluate procedural and in‐hospital outcomes among 150 patients undergoing attempted CTO revascularization utilizing specialized guidewires, microcatheters and guide extensions. The primary endpoint was defined as successful guidewire recanalization and absence of in‐hospital cardiac death, myocardial infarction (MI), or repeat target lesion revascularization (major adverse cardiac events, MACE). Results: The prevalence of diabetes was 32.7%; prior MI, 48.0%; and previous bypass surgery, 32.7%. Average (mean ± standard deviation) CTO length was 46.9 ± 20.5 mm, and mean J‐CTO score was 1.9 ± 0.9. Combined radial and femoral arterial access was performed in 50.0% of cases. Device utilization included: support microcatheter, 100%; guide catheter extension, 64.0%; and mean number of study guidewires/procedure was 4.8 ± 2.6. Overall, procedural success was achieved in 75.3% of patients. The rate of successful guidewire recanalization was 94.7%, and in‐hospital MACE was 19.3%. Achievement of TIMI grade 2 or 3 flow was observed in 93.3% of patients. Crossing strategies included antegrade (54.0%), retrograde (1.3%) and combined antegrade/retrograde techniques (44.7%). Clinically significant perforation resulting in hemodynamic instability and/or requiring intervention occurred in 16 (10.7%) patients. Conclusions: In a multicenter, prospective registration study, favorable procedural success was achieved despite high lesion complexity using antegrade and retrograde guidewire maneuvers and with acceptable safety, yet with comparably higher risk than conventional non‐CTO PCI.